PENANAMAN NILAI TOLERANSI MELALUI PEMBELAJARAN ISMUBA DI SMK MUHAMMADIYAH 2 TULUNGGUNG - Muslih, Muslih; Faridi, Faridi; Romelah, Romelah (Ta'allum: Jurnal Pendidikan Islam, 2021)
Abstract: This study aims to describe the value of tolerance instilled in SMK Muhammadiyah 2 Tulungagung and the process of planting it to students. This research uses a qualitative approach with the type of case study, the place of research is at SMK Muhammadiyah 2 Tulungagung. The research data were obtained from the principal, Ismuba teacher and students using observation, interview and documentation techniques. Data analysis uses data reduction, data presentation and conclusion drawing by checking the validity of the data in the form of credibility and confirmability. The results showed that the cultivation of tolerance values ​​in SMK Muhammadiyah 2 Tulungagung was carried out through Ismuba learning materials which contained tolerance values. The process of planting through active learning both in terms of theory and practice. In ensuring success in instilling the value of tolerance, the school makes direct observations of both the status of active students and alumni. They are monitored regularly without them knowing by involving all teachers. From this evaluation, it was found that there were no cases of intolerance and blasphemy against multicultural values ​​by active students and alumni